2000
DOI: 10.1161/01.hyp.35.4.931
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Hypertrophy in Subcutaneous Small Arteries of Patients With Renovascular Hypertension

Abstract: Abstract-Structural alterations of small arteries in patients with essential hypertension are characterized by inward eutrophic remodeling. However, small arteries in patients with secondary hypertension, as well as in experimental models of hypertension with high circulating renin, are characterized by inward hypertrophic remodeling, which is characterized by smooth muscle cell hypertrophy in animal models. The aim of our study was to determine whether remodeling of subcutaneous small arteries in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 39 publications
3
66
0
1
Order By: Relevance
“…16 Our data showing that chronic NE infusion in mice does not evoke any effect on vascular growth could appear to be in conflict with these previous observations. However, Rizzoni et al 17 recently observed eutrophic vascular remodeling in patients with pheochromocytoma similar to that observed in essential hypertensives, with no changes in the vascular smooth muscle cell component, which, in contrast, is significantly increased in patients with renovascular hypertension. Thus, it must be emphasized again that because the vasculature is a highly differentiated organ system composed of multiple cell types, a number of other factors, which are lacking in the cell culture system, can concomitantly participate in vascular remodeling, which confirms the limitations of comparing in vitro and in vivo experiments.…”
Section: Discussionsupporting
confidence: 57%
“…16 Our data showing that chronic NE infusion in mice does not evoke any effect on vascular growth could appear to be in conflict with these previous observations. However, Rizzoni et al 17 recently observed eutrophic vascular remodeling in patients with pheochromocytoma similar to that observed in essential hypertensives, with no changes in the vascular smooth muscle cell component, which, in contrast, is significantly increased in patients with renovascular hypertension. Thus, it must be emphasized again that because the vasculature is a highly differentiated organ system composed of multiple cell types, a number of other factors, which are lacking in the cell culture system, can concomitantly participate in vascular remodeling, which confirms the limitations of comparing in vitro and in vivo experiments.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, we could not evaluate the structural alterations of small resistance arteries at cellular levels (vascular smooth muscle cell hypertrophy or hyperplasia), because of the complexity of the techniques needed. 32 In conclusion, the MHS presents cardiac (but not vascular) remodeling, endothelial dysfunction and a peculiar contractile response to NE, compared with the other groups. The increase in systolic blood pressure, together with the observed trend to vascular remodeling observed in the MNA strain support a pathogenic role of a-adducin.…”
Section: Adducin and Small Artery Remodeling D Rizzoni Et Almentioning
confidence: 79%
“…Paper [37], which is also based on the biopsy-test data, studies the enlargement of VSMCs in the small arteries as well. It deals with the arteries in the inner layer of the skin, i.e., the layer of subcutaneous fat.…”
Section: Appendix Main Vibration Injuries In An Slt Thementioning
confidence: 99%